2002
DOI: 10.3892/ijo.21.2.337
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced effects in unirradiated cells: A review and implications in cancer

Abstract: A long-held central dogma of radiation biology has been that the carcinogenic effects of ionizing radiation (IR) are induced by the direct and radiolytic actions of IR on nuclear DNA. Numerous investigations, however, have revealed that several cancer relevant effects of IR can occur in cells that have received only cytoplasmic or plasmalemmal membrane exposure to IR. Further, mounting evidence now indicates that many effects that have been attributed to IR-induced damage to nuclear DNA or that occur following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
82
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 114 publications
0
82
0
1
Order By: Relevance
“…By contrast, a range of evidence has now emerged concerning so-called ''bystander'' responses involving damage to cells that were not directly traversed by ionizing radiation, being located at significant distances from the directly hit cells. Bystander effects were first reported for the endpoint of sister chromatid exchanges (1); since then, they have been observed for many endpoints, including clonogenic survival, chromosome aberrations, apoptosis, micronuclei, in vitro oncogenic transformation, mutation induction, genomic instability, and changes in gene expression (2)(3)(4)(5)(6)(7)(8). In vitro, bystander effects have been observed to be mediated by direct gap-junction signaling (9) as well as by molecules secreted into medium (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, a range of evidence has now emerged concerning so-called ''bystander'' responses involving damage to cells that were not directly traversed by ionizing radiation, being located at significant distances from the directly hit cells. Bystander effects were first reported for the endpoint of sister chromatid exchanges (1); since then, they have been observed for many endpoints, including clonogenic survival, chromosome aberrations, apoptosis, micronuclei, in vitro oncogenic transformation, mutation induction, genomic instability, and changes in gene expression (2)(3)(4)(5)(6)(7)(8). In vitro, bystander effects have been observed to be mediated by direct gap-junction signaling (9) as well as by molecules secreted into medium (10).…”
mentioning
confidence: 99%
“…Almost all bystander-effect studies to date have been carried out by using conventional single-cell in vitro systems that do not have a realistic three-dimensional, multicellular structure (2)(3)(4)(5)(6)(7)(8). A few studies have been reported in monolayer explants (13)(14)(15), but no studies have as yet been reported in normal, threedimensional human tissue.…”
mentioning
confidence: 99%
“…Numerous studies on bystander effects have been observed following external beam irradiation of a variety of cell types in a number of cell culture models, as well as in vivo models (41). Observed bystander effects include genetic alterations (mutations, micronucleus formation), neoplastic transformation, changes in gene expression and cellular redox status, induction of apoptosis, alteration of proliferation, and modulation of cell cycle check points (42).…”
Section: Bystander Effectsmentioning
confidence: 99%
“…These calculations are intended to support basic research into what is referred to as the "bystander effect" for low doses of radiation in very small volumes of biologically-important materials. "Bystander effect" refers to a wide range of effects on unirradiated cells from radiation-exposed neighbors [10][11][12][13][14][15][16]. Although the mechanisms underlying bystander effects are unknown, multicellular crosstalk following exposure to low doses or low-dose rates of ionizing radiations may trigger signal transduction pathways that might deregulate normal cell function in the irradiated, as well as neighboring unirradiated cells, leading to bystander effects.…”
Section: Introductionmentioning
confidence: 99%